"Click saccharides": novel separation materials for hydrophilic interaction liquid chromatography - Guo, Zhimou; Lei, Aiwen; Zhang, Yongping; Xu, Qing; Xue, Xingya; Zhang, Feifang; Liang, Xinmiao (Chemical communications (Cambridge, England), 2007)
Bonded mono-, di- and oligosaccharides were developed as novel separation materials for HILIC via click chemistry and proven to have excellent chromatographic properties for separation of polar compounds.